2011
DOI: 10.1152/jn.00516.2010
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of D2-class signaling in dopamine-denervated striatum is in part mediated by D3receptors acting on CaV2.1 channels via PIP2depletion

Abstract: The loss of dopaminergic neurons in the substantia nigra compacta followed by striatal dopamine depletion is a hallmark of Parkinson's disease. After dopamine depletion, dopaminergic D 2 receptor (D 2 R)-class supersensitivity develops in striatal neurons. The supersensitivity results in an enhanced modulation of Ca 2ϩ currents by D 2 R-class receptors. However, the relative contribution of D 2 R, D 3 R, and D 4 R types to the supersensitivity, as well as the mechanisms involved, have not been elucidated. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 84 publications
3
37
0
Order By: Relevance
“…BDNF from dopamine neurons is responsible for inducing normal expression of the dopamine D 3 receptor both during development and in adulthood. Recently an electrophysiological study showed that D 2 like receptors supersensitivity following DA depletion can in part be attributed to an enhanced D 3 receptor activity in striatal neurons (Prieto et al, 2011). Take together, all this data indicate that the reduction of D 3 receptor in PD may be attributed to the dopaminergic neuronal loss and a compensatory upregulation of the D 3 receptor in post synaptic neurons might be involved in the D 3 receptor regulation in PD or nonhuman PD models.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF from dopamine neurons is responsible for inducing normal expression of the dopamine D 3 receptor both during development and in adulthood. Recently an electrophysiological study showed that D 2 like receptors supersensitivity following DA depletion can in part be attributed to an enhanced D 3 receptor activity in striatal neurons (Prieto et al, 2011). Take together, all this data indicate that the reduction of D 3 receptor in PD may be attributed to the dopaminergic neuronal loss and a compensatory upregulation of the D 3 receptor in post synaptic neurons might be involved in the D 3 receptor regulation in PD or nonhuman PD models.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this is due to supplementing dopamine to a relatively spared ventral striatum, i.e., ‘overdose theory’ (Cools 2006; Voon et al 2011b) or dopamine denervation-induced receptor supersensitivity of D3 receptors in the ventral striatum (Prieto et al 2011; Vriend et al 2014b) is still unknown (Fig. 1).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Furthermore the LID develops gradually over time and D2Rs, despite dopamine denervation increases the mRNA levels and protein, D2Rs are not further elevated in LID neither in animal models nor postmortem studies, as a matter of fact in PD patients L-DOPA normalizes the upregulation [157,158]. By then it was unclear whether or not the D3Rs subtype was participating in the supersentitivity by dopamine denervation, however their low expression in striatum made focus the attention in D2Rs [159,160]. In the last decade, D3Rs attracted the attention, it's important to mention that the helical transmembrane spanning region (TMS) of D2Rs and D3R receptors share 75-80% homology in amino-acid sequence and the TMS is directly involved in the orthosteric-binding site, main reason why targeting D3R has been challenging, however D3Rs-preferring compounds have been developed making possible the study of the role of D3Rs in PD.…”
Section: Alterations Of Dopamine Receptors In Neurodegenerative Diseasesmentioning
confidence: 99%